Pneumatic Compression for Embolic Protection During Upper Extremity Endovascular Intervention. (January 2014) - Cassar, Andrew; Barsness, Gregory W.; Wysokinski, Waldemar E.; Gifford, Shaun M.; Bower, Thomas C.; Edwards, William D.; Gulati, Rajiv
Embolic protection devices are occasionally employed during endovascular interventions to prevent complications caused by embolic debris. However, these devices have imperfect efficacy, confer risk of endovascular trauma, and are expensive. We report a patient with giant cell arteritis and symptomatic axillary artery stenosis, with a perceived elevated risk of distal embolization during endovascular intervention. We describe a straightforward embolic protection technique of brachial pressure cuff inflation during endovascular intervention and aspiration of displaced thrombotic material from the static column of blood. This novel, effective, and cost-free technique could also be employed in other vascular beds during endovascular intervention.